الرقابة على مؤسسات التمويل الصغير - ادلبي منى; سعد الدين فراس (Latakia University Journal - Economic and Legal Sciences Series, 2016)
استجابةً لطلبات الخدمات المالية المقدمة من الأفراد ذوي الدخول المتدنية والمنتشرين بكثرة في جميع أنحاء العالم، ظهرت صناعة مالية جديدة مساعدة عُرفت باسم التمويل الصغير ، ففي الدول النامية ونتيجة للحاجة المُلحة لوجود خدمات مالية كالتوفير والاقراض والتأمين وتحويل الأموال إلى أفراد لا تقدم لهم هذه الخدمات بغير ذلك ، نجد أنها غير متطورة أو حتى غير موجودة . وباعتبار أن التنمية الاقتصادية تعتبر الهاجس الرئيس للدول النامية ، وأن تحقيق لأي تقدم لا يتم إلا بتفاعل ومشاركة جميع القطاعات في المجتمع ، ظهرت مؤسسات تقوم بتقديم تلك الخدمات ، فكان من الضروري الاحاطة بجوانب عمل هذه المؤسسات من قبل السلطات المالية في الدولة لاختلافه عن طبيعة عمل البنوك والوقوف على الرقابة التي يتوجب تطبيقها تحقيقاً للغاية من انشائها , ومعرفة دور المصرف المركزي في الحفاظ على دوام واستمرار عملها . وفي هذا الاطار هدف الباحث إلى دراسة مفهوم التمويل الصغير للوقوف على ميزاته وخصائصه ومعرفة المعوقات التي قد تعترض نجاحه ، وذلك في محاولة الوصول إلى معرفة طريقة الرقابة الأنسب والواجب مراعاتها عليه كنشاط مالي مختلف عن باقي الأنشطة المالية و المؤثرة في الدولة ومعرفة دور البنوك المركزية في دعم وتطوير هذه الصناعة. والوصول إلى النتائج التي تساعد على فهم طبيعة عمل مؤسسات التمويل الصغير وبيان عملاءه الذين يجب عليهم الاستفادة من خدماته , بالإضافة إلى تقديم بعض الحلول للمسائل التي يمكن أن تحد من معوقات استمرارية ودوام عمل تلك المؤسسات , مع بيان طبيعة ووظيفة البنوك المركزية في دعم واستمرار هذه الصناعة . In response to requests for financial services from individuals to low-income and spread widely across the world, a new financial industry appeared to help, known as microfinance, in developing countries as a result of the urgent need for the existence of financial services such as savings and loans, insurance and transfer of funds to the members do not provide them with these services otherwise , we find that it is sophisticated or even non-existent. Given that economic development is a concern to developing countries, the President, and that achieving any progress is not only the interaction and participation of all sectors of society, institutions providing these services have emerged, it became necessary to note aspects of the work of these institutions by financial authorities in the state of disagreement about the nature of the work of banks and stand on censorship that must be applied to achieve the very inception. And knowledge of the role of the central bank to maintain the time and the continuation of their work. In this context, the goal of the researcher to study the concept of micro-finance to determine the features, characteristics and knowledge of the obstacles that might hinder the success, in an attempt to access the knowledge of the control method most appropriate and to consider it as an activity Mali different from the rest of the financial activities and influence in the country and find out the role of central banks in support The development of this industry .And access to results that help to understand the nature of the work of microfinance institutions and the statement of its clients who must make use of its services, in addition to providing some solutions to issues that could reduce the obstacles to the continuity and sustainability of the work of those institutions, and the statement of the nature and function of central banks to support the continuation of the industry.